China’s Great Firewall: Cybersecurity as Strategy for Building World Cyberpower - Wowor, Harvardry Gerald Abraham; Sudirman, Arfin; Hakiki, Falhan (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
The information, communication, and technology (ICT) sector has grown significantly in China. One of the advancements they have seen is in the area of cybersecurity. China's growing cybersecurity competence enabled it to create the Great Firewall of China (GFW), a set of control and censorship regulations for internet communications in China. This article investigates the significance of cybersecurity in the development of China's authoritarian authority, with a focus on the GFW as a strategic component. The concepts of cybersecurity and cyberpower served as the article's theoretical foundation. Through interviews and literature reviews, this article employs qualitative methodologies. Â This article demonstrates how China employs GFW to protect its citizens from cyber-attacks by focusing on political risks. China's cyber power is likewise increasing.